Comprehensive Profiling of Protein Ubiquitination for Drug Discovery - Xu, Guoqiang; Jaffrey, Samie R. (Current Pharmaceutical Design, 2013)
Alterations of the ubiquitin proteasome system (UPS) contribute to the progression of many diseases, such as cancer, neurodegenerative diseases, immunological disorders, and inflammation. Pharmacologic inhibition of specific ubiquitin regulatory enzymes and ubiquitination events is an important challenge in drug discovery. Identifying the substrates of the various enzymes that participate in the UPS is needed to determine which enzymes are potential drug candidates. Additionally, identifying the ubiquitination events regulated by pharmacological drugs can potentially discover new applications. In this review we describe mass spectrometry-based proteomic approaches for the identification of ubiquitinated proteins and their modification sites on a proteome-wide scale, focusing on the ubiquitin remnant profiling, a newly developed ubiquitination profiling technique. We then discuss the application of this approach for the profiling of ubiquitination events regulated by cell signaling pathways and explore its future applications for drug discovery in the UPS.
Keywords: ubiquitin remnant profiling